2014
DOI: 10.1177/1362361314531340
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety in Asperger’s syndrome: Assessment in real time

Abstract: Anxiety is a major problem for many people with Asperger's syndrome who may have qualitatively different fears from a non-Asperger's syndrome population. Research has relied on measures developed for non-Asperger's syndrome populations that require reporting past experiences of anxiety, which may confound assessment in people with Asperger's syndrome due to problems with autobiographical memory as are often reported in this group.Experience sampling methodology was used to record real-time everyday experiences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 43 publications
(52 reference statements)
1
31
0
Order By: Relevance
“…Initial disagreement regarding eligibility of 12 studies was resolved through discussion. Specifically, nine studies were included (Gillberg, Helles, Billstedt, & Gillberg, 2015;Gotham, Bishop, Brunwasser, & Lord, 2014;Gotham, Unruh, & Lord, 2014;Hagberg, Billstedt, Nyden, & Gillberg, 2015;Hagberg, Nyden, Cederlund, & Gillberg, 2013;Hare, Wood, Wastell, & Skirrow, 2014; Maddox Running Head: PSYCHOSOCIAL OUTCOMES OF ADULTS WITH ASD were not deemed eligible (Bejerot, Eriksson, & Mortberg, 2014;Gray et al, 2014;Hare, Gracey, & Wood, 2015). Two articles (Gotham, Bishop, et al, 2014;Gotham, Unruh, et al, 2014) employed the same sample, but analysed a different set of variables.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Initial disagreement regarding eligibility of 12 studies was resolved through discussion. Specifically, nine studies were included (Gillberg, Helles, Billstedt, & Gillberg, 2015;Gotham, Bishop, Brunwasser, & Lord, 2014;Gotham, Unruh, & Lord, 2014;Hagberg, Billstedt, Nyden, & Gillberg, 2015;Hagberg, Nyden, Cederlund, & Gillberg, 2013;Hare, Wood, Wastell, & Skirrow, 2014; Maddox Running Head: PSYCHOSOCIAL OUTCOMES OF ADULTS WITH ASD were not deemed eligible (Bejerot, Eriksson, & Mortberg, 2014;Gray et al, 2014;Hare, Gracey, & Wood, 2015). Two articles (Gotham, Bishop, et al, 2014;Gotham, Unruh, et al, 2014) employed the same sample, but analysed a different set of variables.…”
Section: Resultsmentioning
confidence: 99%
“…Appraisals and Coping Skills. Six studies examined the relationship between self-appraisals and coping skills and psychosocial outcomes (Abell & Hare, 2005;Gotham, Bishop, et al, 2014;Hare et al, 2014;Hill et al, 2004;Khanna et al, 2014;Renty & Roeyers, 2006). In a large cross-sectional study (n = 291), Khanna et al (2014) reported that maladaptive coping strategies (i.e., behavioural disengagement, denial, self-blame, self-distraction, substance abuse and venting) were significantly related to poorer physical and mental health-related QoL in adulthood.…”
Section: Factors Associated With Psychosocial Outcomesmentioning
confidence: 99%
“…Nevertheless, only a minority of participants was able to self-report, and the impact of some suggested adaptations (to wording, content, mode of presentation, or scoring; cf. Hare et al 2015; Hong et al 2016; Power and Green 2010) to increase participation, remains unknown. Instead, Tavernor et al (2013) recommend the development of a syndrome specific measure of QoL, constructed with the active involvement of individuals with autism and their families.…”
Section: Discussionmentioning
confidence: 99%
“…The HADS is a commonly used, 14-item self-report screening tool for anxiety and depression. It has demonstrated excellent psychometric properties and is used routinely in clinical and research contexts, including in adult ASD populations [Abell & Hare, 2005;Hare, Wood, Wastell, & Skirrow, 2015;Kanai et al, 2011;Luke, Clare, Ring, Redley, & Watson, 2011].…”
Section: Screening Questionnairesmentioning
confidence: 99%